Handbook of research on mobile software engineering : design, implementation, and emergent applications - Alencar, Paulo, 1957-; Cowan, D. D. 1938- (Engineering Science Reference, 2012)
"This book highlights state-of-the-art research concerning the key issues surrounding current and future challenges associated with the software engineering of mobile systems and related emergent applications"--Provided by publisher.
Keywords: Mobile computing -- Handbooks, manuals, etc.; Mobile computing -- Research -- Handbooks, manuals, etc.; Software engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books